Insights on Bloom Forming Jellyfish (Class: Scyphozoa) in the Gulf of Mexico: Environmental Tolerance Ranges and Limits Suggest Differences in Habitat Preference and Resistance to Climate Change Among Congeners - Frolova, Alexandra; Miglietta, Maria Pia (Frontiers in Marine Science, 2020)
Jellyfish are important components of marine foodwebs and form problematic blooms that negatively impact human enterprise. Jellyfish of the genus Aurelia (Class Scyphozoa) are common bloom-formers in the Gulf of Mexico (GoM). Aurelia have a multi-modal lifecycle where the perennial polyp produces seasonal medusae. Abiotic tolerance ranges and limits strongly influence the distribution of marine species but are unknown for most jellyfish species. Tolerance limits for survival are crucial to understanding present polyp distribution and how distribution may change in climate change scenarios. We sampled and barcoded two Aurelia species from the GoM, namely Aurelia sp. 9 and a possible new species found offshore (Aurelia sp. new). Planulae obtained from one medusa of Aurelia sp. new, and five medusae of Aurelia sp. 9 were used to establish laboratory cultures. Polyps of Aurelia coerulea, a species native to Japan but introduced in North America, Australia, and Europe, were obtained from a local aquarium, barcoded, and used to establish laboratory cultures. Using controlled laboratory experiments, we determined the temperature and salinity limits for polyp survival of the two GoM species and A. coerulea. We find that A. sp. 9 and A. coerulea were tolerant of a broad range of temperatures and salinities, but differed in tolerance limits, suggesting potential differences in habitat and resistance to climate change. A. sp. 9 was most tolerant of high temperatures and low salinities, such as those found in the estuaries of the GoM. Summer high temperatures in the coastal GoM exceed the upper thermal tolerance limit of A. sp. new and A. coerulea, suggesting that A. sp. new is an offshore species and that the coastal GoM waters may not be a suitable environment for A. coerulea. Based on the upper thermal limits identified in this study, the 4°C ocean temperature increase projected for the GoM by the next century may negatively impact Aurelia sp. 9 and Aurelia sp. new populations and is expected to deter Aurelia coerulea from invading the GoM. This is the first account of Aurelia sp. new and the first report of temperature and salinity ranges and tolerance limits for Aurelia species.